Half‐normal saline versus normal saline for irrigation of open‐irrigated radiofrequency catheters in atrial fibrillation ablation. (26th February 2021) - Gianni, Carola; Gallinghouse, G. Joseph; Al‐Ahmad, Amin; Horton, Rodney P.; Bailey, Shane M.; Burkhardt, J. David; Bassiouny, Mohamed A.; MacDonald, Bryan C.; Quintero Mayedo, Angel; Della Rocca, Domenico G.; Mohanty, Sanghamitra; Trivedi, Chintan; et al.
Abstract: Background: The creation of effective and permanent lesions is a crucial factor in determining the success rate of atrial fibrillation (AF) ablation. By increasing the efficacy of radiofrequency (RF) energy‐mediated lesion formation, half‐normal saline (HNS) as an irrigant for open‐irrigated ablation catheters has the potential to reduce procedural times and improve acute and long‐term outcomes. Methods: This is a double‐blind randomized clinical trial of 99 patients undergoing first‐time RF catheter ablation for AF. Patients enrolled were randomly assigned in a 1:1 fashion to perform ablation using HNS or normal saline (NS) as an irrigant for the ablation catheter. Results: The use of HNS is associated with shorter RF times (26 vs. 33 min; p  = .02) with comparable procedure times (104 vs. 104 min). The rate of acute pulmonary vein reconnections (16% vs. 18%) was comparable, with a median of 1 vein reconnection in the HNS arm versus 2 in the NS arm. There was no difference in procedure‐related complications, including the incidence of postprocedural hyponatremia when using HNS. Over the 1‐year follow‐up, there is no significant difference between the HNS and NS with respect to the recurrence of any atrial arrhythmia (off antiarrhythmic drugs [AAD]: 47% vs. 52%; hazard ratio [HR]: 1.17, 95% confidence interval [CI]: 0.66–2.06; off/on AAD: 66% vs. 66%, HR: 1.06, 95% CI: 0.53–2.12), with a potential benefit of using HNS when considering the paroxysmal AF cohort (on/off AAD 73% vs. 62%, HR: 0.72, 95% CI: 0.19–2.70). Conclusions: In a mixed cohort of patients undergoing first‐time AF ablation, irrigation of open‐irrigated RF ablation catheters with HNS is associated with shorter RF times, with a comparably low rate of procedure‐related complications. In the long term, there is no significant difference with respect to the recurrence of any atrial arrhythmia. Larger studies with a more homogeneous population are necessary to determine whether HNS improves clinical outcomes.